Effects of pegagan (Centella asiatica L.) ethanolic extract SNEDDS (self-nanoemulsifying drug delivery systems) on the development of zebrafish (Danio rerio) Embryos - Nasir, Farida Hayati; Chabib, Lutfi; Fauzi, Silmi; Awaluddin, Rizki; ., Sumayyah; ., Wan Syarifah Faizah; Mohd Nasir, Mohd Hamzah; Nipun, Tanzina Sharmin (Wolters Kluwer Health, 2020)
Introduction: Pegagan is a traditional medicinal plant with three major bioactive properties, triterpenoid, steroids, and saponin. It has the properties of antioxidant, antistress, and wound healing. Pegagan extract is prepared in self-nanoemulsifying drug delivery systems (SNEDDS) to overcome the problem of low water-solubility level. Objectives: This study aimed to observe the effect of pegagan ethanolic extract SNEDDS on the development of zebrafish embryos. Materials and Methods: This study used 12 sets of zebrafish embryos presented in five sets of extract SNEDDS with different concentrations, that is, 20, 10, 5, 2.5, and 1.25 μg, five sets of SNEDDS without extract with different concentrations, that is, 20, 10, 5, 2.5, and 1.25 μg, a set of positive control (3.4-DCA 4 mg/L) with one control set (diluted with water), and a negative control (SNEDDS without extract). The procedure was conducted for 96 h with observations every 24 h. The parameters observed were embryonic coagulation, formation of somites, detachment of tail bud from the yolk, and abnormality of embryoResults: The results showed that in 96 h the 20ppm concentration caused 100% mortality. Embryo abnormality appeared as coagulation of embryo, somite malformation, and abnormal tail. Discussion: There is a correlation between the concentration of SNEDDS and the incidence of embryo coagulation. The malformation in the group of pegagan extract SNEDDS is characterized by cardiac edema, somite malformation, and abnormal tail. Conclusion: Pegagan ethanolic extract SNEDDS of 20ppm can inhibit the development of zebrafish embryos.